Rates of spontaneous mutation among RNA viruses. - Drake, J W (1993)
Simple methods are presented to estimate rates of spontaneous mutation from mutant frequencies and population parameters in RNA viruses. Published mutant frequencies yield a wide range of mutation rates per genome per replication, mainly because mutational targets have usually been small and, thus, poor samples of the mutability of the average base. Nevertheless, there is a clear central tendency for lytic RNA viruses (bacteriophage Q beta, poliomyelitis, vesicular stomatitis, and influenza A) to display rates of spontaneous mutation of approximately 1 per genome per replication. This rate is some 300-fold higher than previously reported for DNA-based microbes. Lytic RNA viruses thus mutate at a rate close to the maximum value compatible with viability. Retroviruses (spleen necrosis, murine leukemia, Rous sarcoma), however, mutate at an average rate about an order of magnitude lower than lytic RNA viruses.